Glucocorticoid use and ischemia‐reperfusion injury in laparoscopic liver resection: Randomized controlled trial - Yasushi Hasegawa; Hiroyuki Nitta; Takeshi Takahara; Hirokatsu Katagiri; Shoji Kanno; Akira Umemura; Yuji Akiyama; Takeshi Iwaya; Koki Otsuka; Akira Sasaki (Annals of Gastroenterological Surgery, 2020)
Abstract Aim Laparoscopic liver resection (LLR) is increasingly carried out worldwide. However, there are concerns regarding ischemia‐reperfusion injury caused by pneumoperitoneum and the Pringle maneuver. It is not clear whether perioperative use of glucocorticoids lowers the risk of ischemia‐reperfusion hepatic injury in LLR as has been reported for open liver resection. The aim of the present study was to investigate the role of perioperative glucocorticoid use in improving hepatic function and surgical outcomes after LLR. Methods In this double‐blind, randomized controlled trial (UMIN000013823), we enrolled 130 patients who presented to our institution for LLR between April 2014 and October 2018. Six patients were excluded, resulting in 124 patients being randomized to either the glucocorticoid or the control group. Preoperatively, patients in the glucocorticoid group received 500 mg methylprednisolone in saline solution, patients in the control group saline solution only. Surgical outcomes and blood parameters were compared between the two groups. Results The Pringle maneuver could not be carried out in 24 patients, resulting in 50 patients in each group being included in the analysis. Postoperatively, total, direct and indirect bilirubin, and C‐reactive protein and interleukin‐6 levels were significantly lower, albumin levels were significantly higher, and prothrombin time was significantly shorter in the glucocorticoid than in the control group. Surgical outcomes were not significantly different between the groups. Conclusion This first report on preoperative glucocorticoid use in LLR showed that it significantly improved postoperative liver function and thus might enhance the safety of LLR.